2020
DOI: 10.1093/jpepsy/jsaa018
|View full text |Cite
|
Sign up to set email alerts
|

Parental Behaviors, Emotions at Bedtime, and Sleep Disturbances in Children with Cancer

Abstract: Background Poor sleep is common for children during cancer treatment, but there is limited understanding of the nature of children’s sleep throughout the treatment trajectory. The current exploratory study used an explanatory sequential mixed method approach to examine quantitative associations among sleep problems in children with cancer, parental behavior, and children’s sleep hygiene, with follow-up qualitative characterizations of children’s sleep across cancer treatment stages. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Prior research has described increased clinical sleep referrals in patients with brain tumors, 32 but other studies have not found differences in sleep by diagnostic groups. 28,33 Although radiation significantly impacts sleep in adult oncology, 34 we did not find a difference in sleep in the current sample.…”
Section: Discussionmentioning
confidence: 47%
“…Prior research has described increased clinical sleep referrals in patients with brain tumors, 32 but other studies have not found differences in sleep by diagnostic groups. 28,33 Although radiation significantly impacts sleep in adult oncology, 34 we did not find a difference in sleep in the current sample.…”
Section: Discussionmentioning
confidence: 47%
“…Caregivers further endorsed changes in family rules around behavioral expectations and screen time, reporting a generally more accommodating style of discipline. This finding adds to existing literature that has documented changes in parenting practices during childhood cancer treatment, 24,28 leading to higher levels of lax parenting behaviors among caregivers of youth with cancer in comparison to those without cancer 10 . Changes in behavioral expectations may seem appropriate during treatment (e.g., accommodating impact of corticosteroid symptoms), 29 but could have negative implications for child emotional and behavioral functioning 10,30 .…”
Section: Discussionmentioning
confidence: 54%
“…Most caregivers reported changes in mealtime, eating, and bedtime/sleep rules and routines during treatment. Children with cancer commonly experience disruptions to eating and sleep during active treatment due to side effects of medication (e.g., nausea, drowsiness) and hospitalization (e.g., environmental factors such as lights, noises, and change in food environment) 23,24 . Treatment‐related eating and sleep disturbances can cause caregivers to relax rules and routines (i.e., accommodating) in attempts to meet the child’s needs in the moment 24–26 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations